Failure analysis and materials development of gas turbine blades. (2020) - Swain, B.; Mallick, P.; Patel, S.; Roshan, R.; Mohapatra, S.S.; Bhuyan, S.; Priyadarshini, M.; Behera, B.; Samal, S.; Behera, A.
Abstract: In the current review, the failure analysis of gas turbine blades and to overcome those failures the development of materials have been discussed. The properties of a gas turbine blades should have exhibit have been reported in the current review. In addition to the above, the importance of coating in gas turbine blade has been listed. After the brief investigation of the failure analysis and materials developed it is observed that still there are some properties to be developed to obtain an optimum gas turbine blade.